DAMPAK KESIAPAN MAHASISWA DALAM MENGAMBIL MATA KULIAH PEMBIMBING DAN TEOLOGI PERJANJIAN BARU TERHADAP HASIL BELAJAR - Pujiati (Universitas Kristen Immanuel, 2019)
One of the objectives of this research is to understand how far students are prepared to take the New Testament Theology. This subject is so important because it can lead students to be directed to have a good life and they can grow in God. In studying theology too, every believer comes to understand the purpose of God in His Word which is about the great saying